Área foliar e evapotranspiração de callas cultivadas em substrato em função do nível freático - Muçouçah, Mariana Fraga Soares [UNESP]; Klar, Antonio Evaldo [UNESP]; Muçouçah, Fernando Juabre [UNESP] (My University, 2006)
The objective of this study was to determine the influence of five different water levels on the crop development of Calla. The crop parameters evaluated were leaf area and evapotranspiration. The study was conducted in glass greenhouse with 50% of sunlight reduction. The plants were grown in PVC pots with 150 mm diameter, which were filled with substrate. The plant tubers weighed from 10 g to 12 g. The pots were placed within containers, under water level constant automatically.. The table water levels used were 10, 17, 24, 31 and 38 cm. Nine evaluations during the growth cycle checked the growth development. The evaporation varied from 26.89 to 46.14 L.plant-1 for 38 and 10 cm water levels, respectively and leaf area per plant showed 1011.6 to 2016.3 for the same levels. The substrate water was more available in the treatment 24 cm, with more restrictions in the upper and lower treatments. There was positive correlation between leaf area and evapotranspiration at the final of the culture.
Callas leaf area and evapotranspiration cultivated in substrate at different table water levels
Keywords: Flowers's cultive; Tuber; Zantedeschia; Crops; Cultivation; Evapotranspiration; Plants (botany); Water levels; Water treatment; crop production; evapotranspiration; leaf area; water level; water table; Calla; Tuber (truffle)